2018
DOI: 10.1002/gps.5008
|View full text |Cite
|
Sign up to set email alerts
|

Depression and excess mortality in the elderly living in low‐ and middle‐income countries: Systematic review and meta‐analysis

Abstract: Objective To investigate the association between depression and mortality in the elderly living in low‐ and middle‐income countries. Methods A systematic review and meta‐analysis was performed. We searched in five electronic databases for observational studies investigating the association between mortality and depression. Two reviewers worked independently to select articles, extract data, and assess study quality. Results A total of 10 studies including 13 828 participants (2402 depressed and 11 426 nondepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 41 publications
2
33
1
4
Order By: Relevance
“…The results of this study suggest a negative impact of depression and anxiety on mortality in older people living in LMICs. This corresponds to the majority of existing studies in high‐income countries and a recent review on LMICs . A meta‐analysis on mortality rates in clinical and subthreshold depression has summarised 22 studies and suggested a 60% increased mortality risk for clinical cases and 30% for subthreshold levels .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results of this study suggest a negative impact of depression and anxiety on mortality in older people living in LMICs. This corresponds to the majority of existing studies in high‐income countries and a recent review on LMICs . A meta‐analysis on mortality rates in clinical and subthreshold depression has summarised 22 studies and suggested a 60% increased mortality risk for clinical cases and 30% for subthreshold levels .…”
Section: Discussionsupporting
confidence: 52%
“…Given cultural variation and the complexity of assessment and diagnosis, these results based on highly selected populations might be biased and there is limited evidence from population‐based studies. A recent systematic review which focused on depression and mortality in older people identified 10 population‐based studies from LMICs . Although the pooled effect size was similar to high‐income countries, the high heterogeneity reported in the review might be attributed to variation in diagnostic methods and study design .…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status, for instance, heavily impacts on health and could be partly responsible of the observed association [ 17 ]. Nonetheless, depression has been found associated with increased mortality both in low- and high-income countries [ 18 ].…”
Section: Depression Increases Mortalitymentioning
confidence: 99%
“…Depression is underdiagnosed and undertreated 1 , especially for those who were undergoing adverse events such as COVID-19 pandemic 4 . Given the increased risk of disability and mortality associated with depression 5,6 , it is vitally important to consider preventive interventions that improve the health and quality of life of older adults, and reduce the burden on families and societies. Potentially useful interventions that prevent depression include cognitive and behavioral interventions, such as mindfulness-based therapy and lifestyle interventions 7,8 .…”
Section: Introductionmentioning
confidence: 99%